Law on Health Insurance - The National Assembly (2008)
This Law provides the health insurance regime and policies, including participants, premium rates, responsibilities and methods of payment of health insurance premiums; health insurance cards; eligible health insurance beneficiaries; medical care for the insured; payment of costs of medical care covered by health insurance; health insurance fund; and rights and responsibilities of parties involved in health insurance. This Law applies to domestic and foreign organizations and individuals in Vietnam that are involved in health insurance. This Law does not apply to commercial health insurance